2012
DOI: 10.1007/s12206-011-1037-0
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence modeling of natural convection in enclosures: A review

Abstract: In this paper a review of recent developments of turbulence models for natural convection in enclosures is presented. The emphasis is placed on the effect of the treatments of Reynolds stress and turbulent heat flux on the stability and accuracy of the solution for natural convection in enclosures. The turbulence models considered in the preset study are the two-layer k ε − model, the shear stress transport (SST) model, the elliptic-relaxation (V2-f) model and the elliptic-blending second-moment closure (EBM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Zhang et al (2007) evaluated various turbulence models in predicting airflow and turbulence flow in enclosed environments. Choi and Kim (2012) reviewed several recent developments of turbulence models for natural convection in enclosures. Gupta et al (2011) studied the transport of expiratory droplets in an aircraft cabin and found that the bulk airflow pattern in cabin played the most important role on the droplet transport.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2007) evaluated various turbulence models in predicting airflow and turbulence flow in enclosed environments. Choi and Kim (2012) reviewed several recent developments of turbulence models for natural convection in enclosures. Gupta et al (2011) studied the transport of expiratory droplets in an aircraft cabin and found that the bulk airflow pattern in cabin played the most important role on the droplet transport.…”
Section: Introductionmentioning
confidence: 99%
“…The point thermal transmittance TT3D (W/K) of the light guides was calculated. The TT3D is defined in standard ISO 10211 [29] for steady state heat transfer and for temperature difference between the environments on either side of a thermal bridge:…”
Section: Resultsmentioning
confidence: 99%
“…and indoor and outdoor temperatures are defined in accordance with standard values [29]. The 2D model of light guides was studied for thermal and air flow distribution under the defined boundary conditions.…”
Section: The Final 2d Simplified Modelmentioning
confidence: 99%
“…Literature review on performance of turbulence models Se observa que muchos autores han evaluado los modelos k-ω estándar y k-ω SST para NC, los que muestran un excelente desempeño para predecir la temperatura y la velocidad. Un par de estudios (Choi & Kim, 2012; también han mostrado un excelente desempeño del modelo v2f y su variable v2f-dav para NC.…”
Section: Evaluación De Los Modelos De Turbulenciaunclassified